Mixed Adeno-Neuroendocrine Carcinoma; Case Series of Ten Patients with Review of the Literature - Yiğit Düzköylü; Orhan Aras; Erdal Birol Bostancı; Tülay Keklik Temuçin; Murat Ulaş (Balkan Medical Journal, 2018)
Aims: Mixed adeno-neuroendocrine carcinoma is a rare entity, diagnosed with immunohistochemical studies. Literature mainly includes case reports and series which are very few. In our study, we aimed to report a case series from a tertiary hospital with demographics of the patients, detailed tumor and clinical findings and follow-up plus survival conditions. Methods: Pathology database was explored for patients with the pathological diagnosis of ‘mixed adeno-neuroendocrine carcinoma’ and patients were identified retrospectively and evaluated in means of demographics, histopathological examination, tumor properties.Results: Ten patients had been diagnosed with mixed adeno-neuroendocrine carcinoma in our center, diagnosed at a mean age of 64.7. Stomach was found to be the most common localization. Five patients (50%) were diagnosed as grade 3. Following surgery, median follow-up was 15 months with a median survival time of 20.6 months. Conclusion: This case series may contribute to the literature on the pathological and clinical aspects of the mixed adenoneuroendocrine carcinoma of the gastrointestinal system.